MicroRNA 15a/16‐1 suppresses aryl hydrocarbon receptor–dependent interleukin‐22 secretion in CD4+ T cells and contributes to immune‐mediated organ injury. Issue 3 (1st February 2018) - Lu, Zhou; Liu, Jiajing; Liu, Xiaoming; Huang, Enyu; Yang, Jiao; Qian, Jiawen; Zhang, Dan; Liu, Ronghua; Chu, Yiwei
Abstract : Interleukin‐22 (IL‐22), as a link between leukocytic and nonleukocytic cells, has gained increasing attention for its pronounced tissue‐protective properties. MicroRNAs, emerging as crucial immune modulators, have been reported to be involved in the production and action of various cytokines. However, the precise control of IL‐22 by microRNAs and its subsequent actions remained to be elucidated. In this study, we found a negative correlation between the expression of microRNA 15a/16‐1 (miR‐15a/16‐1) and IL‐22 in the model of concanavalin A–induced, immune‐mediated liver injury. Knockout of miR‐15a/16‐1 ameliorated liver injury in an IL‐22‐dependent manner. Further results revealed that cluster of differentiation 4–positive (CD4 + ) T cells were the major source of IL‐22 during liver injury and that the aryl hydrocarbon receptor was the direct target of miR‐15a/16‐1 in CD4 + T cells. In vivo and in vitro data showed that miR‐15a/16‐1 knockout CD4 + T cells produced more IL‐22, while overexpression of miR‐15a/16‐1 down‐regulated the IL‐22 production by inhibiting the aryl hydrocarbon receptor. Moreover, transfer of miR‐15a/16‐1 knockout CD4 + T cells promoted tissue repair compared to wild‐type CD4 + T cells by up‐regulating IL‐22. In addition, as a synergistic effect, IL‐22 could down‐regulate miR‐15a/16‐1 expression by activating phosphorylated signal transducer and activator of transcription 3‐c‐myc signaling, and the decrease of miR‐15a/16‐1 in damaged hepatocytes contributed to IL‐22‐mediated tissue repair by reducing cell apoptosis and promoting cell proliferation. As further proof, we demonstrated the role of miR‐15a/16‐1 in controlling IL‐22 production and IL‐22‐mediated reconstruction of the intestinal epithelial barrier in a dextran sodium sulfate–induced colitis model. Conclusion : Our results suggest that miR‐15a/16‐1 acts as a essential regulator of IL‐22 and that the miR‐15a/16‐1–aryl hydrocarbon receptor–IL‐22 regulatory axis plays a central role in tissue repair; modulation of miR‐15a/16‐1 might hold promise in developing new strategies to enhance IL‐22‐mediated tissue repair. (Hepatology 2018;67:1027–1040)